A Traditional Novel Approach for Skill Enhancement of Teaching-Learning Process in Engineering Education - Aluvala, Srinivas; Pothupogu, Soumya (Journal of Engineering Education Transformations, 2015)
In the modem day of technological competitiveness where world is demanding more technological developments which need to meet the present scenario problems. There is an urgent need of skilled engineers, as of now this need is not fulfilled by our engineering educational programs. Because there is a large gap between the educational structure and the societal demands, this has to be bridged by restructuring the engineering education. With this paper we come up with an approach of restructuring the engineering educational programs curriculum that bridge the gap and steer up the skills in the engineering students. An engineer should be basically a problem solver, who should own the capability to analyze and evaluate the problems arise in the society, at present we are in dire need of such engineers for the societal up gradation. In this paper, our view of initial attempt to restructure the curriculum of engineering education based on traditional age old learning will be shared. We evaluate student learning outcomes based on the practical assignment assessment results and their success in the implementation. With minor modifications in the present system and including the best of traditional year wise learning approach in engineering education can bring a radical change, create greater impact on students to make them industry ready and problem solvers of society.